Malaysia : Background Paper. (IMF Staff Country Reports; Country Report, 1996)
This Background Paper on Malaysia examines developments and trends in the labor market since the mid-1980s. The paper describes the changes in the employment structure and the labor force. It reviews wages and productivity trends and their effects on unit labor cost. The paper highlights that Malaysia's rapid growth, sustained since 1987, has had a major impact on the labor market. The paper outlines the major policy measures to address the labor constraints. It also analyzes Malaysia's recent experience with international capital flows.